Pseudoephedrine: A potential risk of doping in sport - Antić Dušan (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2016)
Pseudoephedrine is a systemic decongestant. It is commonly used in treatment of nasal and sinus congestion in conditions such as cold, flue or allergy. In adittion to its use as drug, pseudoefedrine can be abused in sports as doping agents. On the List of prohibited substanes in sport, pseudoephedrine can be found in the group of Stimulants. Pseudoefedrin is widely used all around the world and many combination of products containing pseudoephedrine could be easily sold without prescription. That is the main reason why athletes could be accidentally doping positive. Nevertheless, any doping is a doping. Athletes must use medications with caution, esspecially those medications containing some doping agents.